2011
DOI: 10.1016/j.beha.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hematological malignancies with nonmyeloablative, HLA-haploidentical bone marrow transplantation and high dose, post-transplantation cyclophosphamide

Abstract: Hematopoietic stem cell transplantation provides the only potential curative option in many patients with hematological malignancies. Finding a suitably matched donor in a timely manner is often difficult. However, most patients have a partially HLA-mismatched (HLA-haploidentical) first-degree relative readily available. Historically, HLA-haploidentical bone marrow transplantation (BMT) has been considered extremely high risk due to high rates of life-threatening graft-versus-host disease (GVHD) and non-relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 53 publications
(50 reference statements)
1
38
0
1
Order By: Relevance
“…At the end of last century, one of the major concerns in HID HSCT was the occurrence of fatal acute GVHD (aGVHD). However, strategies including T-cell depletion in vitro, antithymoglobulin (ATG)/intensive immunosuppression or, the latest development, post-transplant cyclophosphamide, have achieved acceptable incidences of acute severe GVHD and even similar clinical outcomes in some cohort studies when compared with those of MSD or unrelated HSCT (Aversa et al, 2005;Wang et al, 2009;Munchel et al, 2011). However, data describing the features and risk factors for GVHD, especially chronic GVHD (cGVHD) after HID HSCT are relatively limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of last century, one of the major concerns in HID HSCT was the occurrence of fatal acute GVHD (aGVHD). However, strategies including T-cell depletion in vitro, antithymoglobulin (ATG)/intensive immunosuppression or, the latest development, post-transplant cyclophosphamide, have achieved acceptable incidences of acute severe GVHD and even similar clinical outcomes in some cohort studies when compared with those of MSD or unrelated HSCT (Aversa et al, 2005;Wang et al, 2009;Munchel et al, 2011). However, data describing the features and risk factors for GVHD, especially chronic GVHD (cGVHD) after HID HSCT are relatively limited.…”
Section: Resultsmentioning
confidence: 99%
“…Human leucocyte antigen (HLA)-identical siblings have historically been the first choice of donors. More recently, HSCT with haploidentical donors (HIDs) selected from family members has shown promising results for patients lacking an HLA-matched sibling (MSD) or unrelated donor (URD) (Aversa et al, 2005;Munchel et al, 2011;Wang et al, 2013). At the end of last century, one of the major concerns in HID HSCT was the occurrence of fatal acute GVHD (aGVHD).…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18]20,21 Recently, the use of post-transplant cyclophosphamide (Cy) has permitted transplantation across major HLA barriers for patients receiving BM from a haploidentical donor. [22][23][24][25][26] The use of posttransplant Cy has several advantages compared with traditional methods of ex vivo T-cell depletion, which include lower complexity and cost, and improved immune reconstitution permitting a more widespread adoption of this transplant procedure. 27 Several studies have confirmed the efficacy and safety of this approach, but most reports have focused on patients with hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…104 This simple in vivo graft manipulation is able to break the HLA barrier by allowing the infusion of haploidentical donor cells with similar or reduced rates of aGVHD compared with transplants using HLAmatched grafts. 105,106 The results of these studies, as well as the results of 3 recently published novel though preliminary aGVHD prophylaxis trials, have prompted new multicenter comparative clinical trials. First, a phase 1/2 study of maraviroc, a CCR5 inhibitor that blocks lymphocyte chemotaxis while preserving effector functions, demonstrated very low rates of grade II-IV acute GVHD (;15%) and no visceral GVHD at day 100 post-HCT in 35 evaluable patients.…”
Section: Prophylaxismentioning
confidence: 99%